VD_FINDINFO HC / 2010 / 76 vom 22. Dezember 2009 - VD Tribunal cantonal (2009)
FAUTE, CRÉANCE, PRÉTENTION DE DROIT PUBLIC | 47 CP, 71 al. 1 CP, 71 al. 2 CP, 411 let. g CPP, 411 let. h CPP, 411 let. i CPP